Use of intraoperative ultrasonography in deciding the extent of surgical decompression for Chiari Malformation Type I - Thapa, Amit; Bohara, Sandeep (Nepal Journal of Neuroscience, 2022)
Introduction: The optimal surgical treatment for Chiari Malformation Type I continues to be controversial with procedures ranging from posterior fossa bone decompression alone to release or resection of the cerebellar tonsils. Intraoperative ultrasonography can be a useful tool in deciding the least invasive procedure so as to reduce the complications and improve the efficacy of the procedure. Methods: A retrospective study over a period of seven years of patients who underwent surgery for Chiari Malformation type I under the guidance of intraoperative ultrasonography was done. The patients underwent three types of surgery based on the adequacy of decompression seen as free flow of CSF through foramen of magendie and free movement of cerebellar tonsils on intraoperative ultrasonography placed over the duramater: Group 1: foramen magnum decompression alone, Group 2: foramen magnum decompression and lax duraplasty and Group 3: foramen magnum decompression with lax duraplasty and release or resection of cerebellar tonsils. Outcome of the types of surgery were determined by the clinical outcome at post-operative six months and two years. Result: A total of 10 patients: four males and six females were included in the study. The mean age of the population was 32.7 +/- 14.57 years with range of 42 years. There were three patients in group 1, two patients in group 2 and five patients in group 3. 100% of the patients in group 1, 50% of patients in group 2 and 60% of the patients in group 3 had improved outcome as evidenced by resolution of symptoms and resolution of syrinx at six months and one year postoperative period. Conclusion: Intraoperative ultrasonography is an effective tool in deciding the extent of surgical decompression for Chiari Malformation Type I. A larger multicentre study would help statistically validate the findings.